Implementasi Sensor Suhu KSD pada Sistem Pengendali Kecepatan Kipas DC - Rizal Agri Wahyuadi; Muhammad ‘Atiq; Ahkam Virdaus; Danang Hendrawan; Raka Dian Mahardi; Sigit Prakosa A N (Lembaga Pengembangan Kinerja Dosen, 2025)
Automatic and adaptive fan speed control is an important aspect in maintaining the stable performance of electronic devices, reducing energy consumption, and preventing damage due to excessive temperature. This research focuses on the design and implementation of a DC fan speed control system that utilizes a temperature sensor in the form of a KSD type thermostat as the main regulator. The system is designed to be able to operate at three different speed levels, which are automatically activated based on certain temperature points, namely 31°C, 40°C, and 55°C. Thus, the fan only works according to actual needs, so its use is more efficient. The research method used is a laboratory experimental approach, which includes three main stages, namely electronic circuit design, hardware component assembly, and functional testing of the system. Trials are carried out to ensure that the system is able to respond to temperature changes appropriately and consistently. The test results show that the control system built works according to the design, where the fan can adjust its rotational speed automatically when the temperature reaches a predetermined threshold. Overall, this system has a simple design, is robust to temperature changes, and is effective in controlling heat in electronic devices. Its implementation has the potential to provide significant benefits in the form of energy efficiency, more optimal fan power utilization, and extended device lifespan through stable operating temperature control. This research could form the basis for the development of smarter and more efficient cooling systems in the future.